Guidelines for developing efficient thermal conduction and storage models within building energy simulations. (15th April 2017) - Hillary, Jason; Walsh, Ed; Shah, Amip; Zhou, Rongliang; Walsh, Pat
Abstract: Improving building energy efficiency is of paramount importance due to the large proportion of energy consumed by thermal operations. Consequently, simulating a building's environment has gained popularity for assessing thermal comfort and design. The extended timeframes and large physical scales involved necessitate compact modelling approaches. The accuracy of such simulations is of chief concern, yet there is little guidance offered on achieving accurate solutions whilst mitigating prohibitive computational costs. Therefore, the present study addresses this deficit by providing clear guidance on discretisation levels required for achieving accurate but computationally inexpensive models. This is achieved by comparing numerical models of varying discretisation levels to benchmark analytical solutions with prediction accuracy assessed and reported in terms of governing dimensionless parameters, Biot and Fourier numbers, to ensure generality of findings. Furthermore, spatial and temporal discretisation errors are separated and assessed independently. Contour plots are presented to intuitively determine the optimal discretisation levels and time-steps required to achieve accurate thermal response predictions. Simulations derived from these contour plots were tested against various building conditions with excellent agreement observed throughout. Additionally, various scenarios are highlighted where the classical single lumped capacitance model can be applied for Biot numbers much greater than 0.1 without reducing accuracy. Highlights: Addressing the problems of inadequate discretisation within building energy models. Accuracy of numerical models assessed against analytical solutions. Fourier and Biot numbers used to provide generality of results for any material. Contour plots offer intuitive way to interpret results for manual discretisation. Results show proposed technique promising for automation of discretisation process.